Biochemical Responses and DNA Damage of Chlorella pyrenoidosa H. Chick upon Exposure to Combined Cu and Cd at Environmentally Realistic Levels: DOI: 10.32526/ennrj.18.3.2020.28 - P. Nugroho, Andhika; S.N. Handayani, Niken; Darmasiwi, Sari; G. Zulfikar, Wildan; A. Rizki, Ahmad (Environment and Natural Resources Journal, 2020)
Monitoring aquatic ecosystems is necessary to prevent or reduce the impact of metal pollutants on ecosystems and human health. Biological responses, or biomarkers, can provide quick and direct evidence of exposure to environmental stressors. This study evaluated the sensitivity of biomarkers of Chlorella pyrenoidosa after short-term exposure to combined copper and cadmium at environmentally realistic concentrations with the following biological endpoints: growth; alkaline phosphatase activity; chlorophylls, pheophytin-a, carbohydrate, and protein content; and DNA damage. C. pyrenoidosa was exposed to three combinations of copper and cadmium for 120 min, or for 48 h to assess its DNA damage. To assess the sensitivity of the biological responses to the combined metals, integrated biomarker response (IBR) analysis was also performed. The results demonstrated that exposure to combined Cu and Cd caused an inhibition of growth and activity of alkaline phosphatase, a decrease of chlorophyll-a and -b and protein, and an increase of pheophytin-a and tail factors DNA. The IBR analysis affirmed that the inhibition of alkaline phosphatase activity and the decrease of protein level were responsive biomarkers for exposure to the combined metals.